Architecture and Expression of the Nfatc1 Gene in Lymphocytes - Rudolf, Ronald; Busch, Rhoda; Patra, Amiya K.; Muhammad, Khalid; Avots, Andris; Andrau, Jean-Christophe; Klein-Hessling, Stefan; Serfling, Edgar (Frontiers in Immunology, 2014)
In lymphocytes, the three NFAT factors NFATc1 (also designated as NFAT2), NFATc2 (NFAT1), and NFATc3 (NFAT4 or NFATx) are expressed and are the targets of immune receptor signals, which lead to a rapid rise of intracellular Ca++, the activation of phosphatase calcineurin, and to the activation of cytosolic NFATc proteins. In addition to rapid activation of NFAT factors, immune receptor signals lead to accumulation of the short NFATc1/αA isoform in lymphocytes which controls their proliferation and survival. In this mini-review, we summarize our current knowledge on the structure and transcription of the Nfatc1 gene in lymphocytes, which is controlled by two promoters, two poly A addition sites and a remote downstream enhancer. The Nfatc1 gene resembles numerous primary response genes (PRGs) induced by LPS in macrophages. Similar to the PRG promoters, the Nfatc1 promoter region is organized in CpG islands, forms DNase I hypersensitive sites, and is marked by histone tail modifications before induction. By studying gene induction in lymphocytes in detail, it will be important to elucidate whether the properties of the Nfatc1 induction are not only typical for the Nfatc1 gene but also for other transcription factor genes expressed in lymphocytes.